Nuclease Activity of Diaza-Crown Ether Complexes of Cerium(III) with Different Functional Groups as Side Arms. (March 2018) - Jiang, Bingying; Cai, Shulan; Xie, Jiaqing; Feng, Fa-Mei
Cerium(III) complexes of two ligands of a diaza-crown ether with different functional groups as side arms were synthesised and characterised. The catalytic ability of the cerium(III) complexes for pUC19 DNA cleavage was investigated and compared using agarose gel electrophoresis. The results indicate that the catalytic activity of the complex CeL2 [L2 = 2, 2′- (1, 4, 10, 13-tetraoxa-7, 16-diazacyclooctadecane-7, 16-diyl) diacetamide] with two carbamoylmethyl groups is significantly higher than the complex CeL1 [L1 = 2, 2′- (1, 4, 10, 13-tetraoxa-7, 16-diazacyclooctadecane-7, 16-diyl) diethanol] with two hydroxyethyl groups under the same conditions. The optimum catalytic concentrations of CeL1 and CeL2 were 7.69 × 10 −5 and 3.08 × 10 −5 mol L −1 respectively and excessively high concentrations of the complexes can reduce their catalytic efficiency due to the formation of inactive μ-hydroxo dimers. The optimum catalytic acidities of CeL1 and CeL2 were pH 7.0 and 7.5 respectively and excessively high pH of the reaction system can reduce the catalytic efficiency of the complexes due to the formation of cerium(III) hydroxide. DNA cleavage promoted by the two complexes takes place via the same hydrolytic pathway and so the activity difference of the two complexes is attributed to the stability of the complexes, rather than the catalytic mechanism.